Estimating the Height of An Individual from The Length of Ulna in Undergraduate Students of a Nepalese Medical College - Pandey, Niraj; Padhee, Bandana (Journal of Lumbini Medical College, 2020)
Introduction: Estimation of height from bones plays an important role in identifying unknown bodies, parts of bodies, or skeletal remains. Multiple anthropometric techniques have been used to estimate stature from skeletal remains by anthropologists, anatomists, and forensic experts. The ulna is a long bone often used for body height estimation, as it is mostly subcutaneous throughout its length and is easily approachable for measurement.Methods: The present study was carried out on 100 (57 male and 43 female) undergraduate students of a medical college of the age group of 18 to 24 years. The parameters studied were height, length of right, and left ulna. The observations were analyzed by Pearson’s correlation to examine the relationship between the length of ulna and height.Results: The mean height of males was 174.54 ± 13.32 cm and of females was 156.01±11.19 cm. The mean length of the right ulna was 27.36 ± 2.12 cm (males) and 24.35±1.97 cm (females). The mean length of the left ulna was 27.29 ± 2.13 cm (males) and 24.06 ± 2.18 cm (females). Pearson’s correlation showed a positive and statistically significant (p